2014
DOI: 10.1111/jeu.12136
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Phylogeny of Thelohanellus marginatus n. sp. (Myxozoa: Myxosporea), a Parasite Infecting the Gills of the Fish Hypophthalmus marginatus (Teleostei: Pimelodidae) in the Amazon River

Abstract: Thelohanellus marginatus n. sp., a new myxosporean parasite infecting the primary gill filaments of the teleost fish Hypophthalmus marginatus (Pimelodidae) in the Amazon River, is described on the basis of microscopic and molecular procedures. The parasite forms whitish and ellipsoidal cysts up to 250 μm in diam. Myxospores ellipsoidal with a slightly more pointed anterior end, measuring 17.1 ± 0.6 μm in length, 6.9 ± 0.4 μm in width, and 5.1 ± 0.5 μm in thickness. A single pyriform polar capsule, 9.0 ± 0.3 μm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 20 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…; Rocha et al. ) have also demonstrated a strong correlation between parasites that infect hosts with taxonomic affinity. In the case of Kudoa , the genus is almost exclusively composed of marine species, with only three records from freshwater hosts: K. eleotrisi (Siau ), K. cascasia (Sarkar and Chaudhury ) and K. aequidens (Casal et al.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…; Rocha et al. ) have also demonstrated a strong correlation between parasites that infect hosts with taxonomic affinity. In the case of Kudoa , the genus is almost exclusively composed of marine species, with only three records from freshwater hosts: K. eleotrisi (Siau ), K. cascasia (Sarkar and Chaudhury ) and K. aequidens (Casal et al.…”
Section: Discussionmentioning
confidence: 95%
“…Overall, the phylogenetic analysis of the SSU rRNA gene of several different myxosporean parasites has been demonstrating that the site of infection and the type of aquatic environment inhabited by the fish host are important aspects that influence the evolution and differentiation of Myxosporea (Andree et al 1999;Eszterbauer 2004;Fiala 2006;Holzer et al 2004;Kent et al 2001;Rocha et al 2013). Recent descriptions of myxobolid parasites (Carriero et al 2013;Moreira et al 2013;Rocha et al 2014) have also demonstrated a strong correlation between parasites that infect hosts with taxonomic affinity. In the case of Kudoa, the genus is almost exclusively composed of marine species, with only three records from freshwater hosts: K. eleotrisi (Siau 1971), K. cascasia (Sarkar and Chaudhury 1996) and K. aequidens (Casal et al 2008); all of which were described without the use of molecular tools.…”
Section: Discussionmentioning
confidence: 99%
“…In the phylogenetic analysis, M. curimatae n. sp. appears in a well-supported subclade (bootstrap 100), as a sister species of T. marginatus, a parasite of a South American pimelodid [36], corroborating previous phylogenetic analysis, which showed species of the Thelohanellus genus clustering scattered in the large Myxobolus clade [36][37][38][39]. As suggested by Fiala et al [40], and corroborated by the present and others studies [1,28,41,42], small morphologic variations of the spores, as loss of one polar capsule or development of spore caudal appendages, when confronted with DNA sequence data, seem to be incompatible features to discriminate genera in platysporinid Myxozoa.…”
Section: Discussionmentioning
confidence: 96%
“…For this study, sixteen adult specimens of P. costatus (with average size of 34 [32][33][34][35][36][37][38][39][40] cm) were collected from the São Francisco River, in the city of Pirapora, Minas Gerais state, Brazil (17°12′75″S, 44°50′95″ W) in December 2011. The methodology of the present study was approved by the ethics research committee of Federal University of São Paulo (CEP: 0128/12), and is in accordance with Brazilian law.…”
Section: Methodsmentioning
confidence: 99%
“…The present phylogenetic analysis further demonstrates that all these species show the polyphyletic relationship among them. Rocha et al (2012) found that the tissue specificity and geographical location has been identified as one of the important factors for clustering of species in phylogenetic trees. Various myxobolids inhabiting the same tissue and host clustered together with the present species in the phylogenetic tree.…”
Section: Molecular Comparisonmentioning
confidence: 99%